Readiness Of Road Project Contractors To Use Musharakah: Evidence From Jakarta (Qualitative Study) - Mohamad Torik Langlang Buana; Nuradli Ridzwan Shah Mohd Dali; Amrizal Amrizal; Eko Tama Putra Saratian (Department of Islamic Economics, IPB University&Indonesian Association of Islamic Economist(IAEI), 2026)
Non-Indexed Publication